2012
DOI: 10.1074/mcp.m111.013730
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics in Signal Transduction Pathways Involving Promiscuous Oligomerizing Receptors Can Be Determined by Receptor Specificity: Apoptosis Induction by TRAIL

Abstract: Here we show by computer modeling that kinetics and outcome of signal transduction in case of hetero-oligomerizing receptors of a promiscuous ligand largely depend on the relative amounts of its receptors. Promiscuous ligands can trigger the formation of nonproductive receptor complexes, which slows down the formation of active receptor complexes and thus can block signal transduction. Our model predicts that increasing the receptor specificity of the ligand without changing its binding parameters should resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 62 publications
0
27
0
Order By: Relevance
“…We used Colo205 cells where we have previously shown that neutralisation of DcR1 and DcR2 enhanced WT TRAILinduced apoptosis. 27 Colo205 cells were treated with neutralising antibodies against DcR1 and DcR2 for 1 h before treatment with TRAIL45 mutants for 3 h. The percentage of apoptotic cells was determined using Annexin V. As expected, neutralisation of DcR1 and DcR2 significantly enhanced WT TRAIL-mediated apoptosis, but it had no effect on the pro-apoptotic potency of TRAIL45-a, TRAIL45-c and TRAIL45-d confirming that these mutants have lost the ability to bind to the DcRs and thus provided us with a valuable tool to test the role of DcRs in tissue-level/transregulation of TRAIL sensitivity (Figure 2e). …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…We used Colo205 cells where we have previously shown that neutralisation of DcR1 and DcR2 enhanced WT TRAILinduced apoptosis. 27 Colo205 cells were treated with neutralising antibodies against DcR1 and DcR2 for 1 h before treatment with TRAIL45 mutants for 3 h. The percentage of apoptotic cells was determined using Annexin V. As expected, neutralisation of DcR1 and DcR2 significantly enhanced WT TRAIL-mediated apoptosis, but it had no effect on the pro-apoptotic potency of TRAIL45-a, TRAIL45-c and TRAIL45-d confirming that these mutants have lost the ability to bind to the DcRs and thus provided us with a valuable tool to test the role of DcRs in tissue-level/transregulation of TRAIL sensitivity (Figure 2e). …”
Section: Resultsmentioning
confidence: 97%
“…Using the FoldX protein design algorithm, [23][24][25][26] amino-acid residues that form the ligand receptor-binding interface of TRAIL were mutated in silico to all possible natural aminoacid permutations and the change in the binding energy to all four TRAIL receptors was calculated as described previously. [24][25][26][27] Amino-acid substitutions that increased the energy of interaction between TRAIL-DcR1/DcR2 (that is, reduced binding affinity, positive ΔΔG i ) and mutations that decreased the energy of interaction between TRAIL and DR4/DR5 have been identified (Supplementary Figure 5).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, Reis and colleagues showed that the increased sensitivity to a DR4-selective TRAIL mutant was associated with an increase in the activation of caspase-8 (43). Moreover, Szegezdi and colleagues showed that receptor-selective TRAIL variants enhanced the kinetics of receptor activation and that apoptosis largely depends on the relative amounts of its receptors (44). In melanoma, Kurbanov and colleagues showed that the resistance of cells to DR4-mediated apoptosis was related to the low level of caspase-8 or -10 and DR4 (45).…”
Section: Discussionmentioning
confidence: 99%
“…Receptor-selective TNF family ligands have been previously generated by employing rational design-or directed evolutionbased methods. Rational design approaches have been previously used to design receptor-selective TNF-␣ variants (35) and TRAIL variants (22,23,26,36). Directed evolution methods employing phage display were also used to generate receptorselective TRAIL variants (37), a receptor-selective TNF␣ antagonist (38), and a LIGHT/LT␤ variant that does not bind DcR3 (39).…”
Section: Discussionmentioning
confidence: 99%